Lux in tenebris : the visual and the symbolic in western esotericism - Forshaw, Peter J. (Aries Book Series, 2016)
Lux in Tenebris is a collection of eighteen original interdisciplinary essays that address aspects of the verbal and visual symbolism in the works of significant figures in the history of Western Esotericism, covering such themes as alchemy, magic, kabbalah, angels, occult philosophy, Platonism, Rosicrucianism, and Theosophy. Part I: Middle Ages andamp; Early Modernity ranges from Gikatilla, Ficino, Camillo, Agrippa, Weigel, Böhme, Yvon, and Swedenborg, to celestial divination in Russia. Part II: Modernity andamp; Postmodernity moves from occultist thinkers Schwaller de Lubicz and Evola to esotericism in literature, art, and cinema, in the works of Colquhoun, Degouve de Nuncques, Bruskin, Doitschinoff, and Pérez-Reverte, with an essay on esoteric theories of colour. Contributors are: Michael J.B. Allen, Susanna Åkerman, Lina Bolzoni, Aaron Cheak, Robert Collis, Francesca M. Crasta, Per Faxneld, Laura Follesa, Victoria Ferentinou, Joshua Gentzke, Joscelyn Godwin, Hans Thomas Hakl, Theodor Harmsen, Elke Morlok, Noel Putnik, Jonathan Schorsch, György Szönyi, Carsten Wilke, and Thomas Willard.